2011
DOI: 10.1007/s00894-011-1298-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of the effect of thermal perturbation on the mechanical unfolding of titin I27

Abstract: The emergence of single-molecule force measurement experiments has facilitated a better understanding of protein folding pathways and the thermodynamics involved. Computational methods such as steered molecular dynamics (SMD) simulations are helpful in providing atomistic level information on the unfolding pathways. Recent experimental studies have showed that combinations of single-molecule experiments with traditional methods such as chemical and/or thermal denaturation yield additional insights into the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These configurations of the protein were then resolvated in each of the six pre-equilibrated solvent environments (water and 8 M aqueous urea at 300, 400, and 500 K). Previous studies have suggested that combination of two or more perturbations (chemical, thermal, and mechanical) helps examine different aspects of the protein folding problem that may not be accessible individually. , The size of the solvation box for all the umbrella sampling simulations (74 × 74 × 74 Å 3 ) was chosen based on the initial configuration of the last window so that the box extended at least 12 Å on all sides. Each of the windows was then subjected to short energy minimization and equilibration followed by 50 ns MD simulations, resulting in a cumulative sampling time of about 4.2 μs.…”
Section: Methodsmentioning
confidence: 99%
“…These configurations of the protein were then resolvated in each of the six pre-equilibrated solvent environments (water and 8 M aqueous urea at 300, 400, and 500 K). Previous studies have suggested that combination of two or more perturbations (chemical, thermal, and mechanical) helps examine different aspects of the protein folding problem that may not be accessible individually. , The size of the solvation box for all the umbrella sampling simulations (74 × 74 × 74 Å 3 ) was chosen based on the initial configuration of the last window so that the box extended at least 12 Å on all sides. Each of the windows was then subjected to short energy minimization and equilibration followed by 50 ns MD simulations, resulting in a cumulative sampling time of about 4.2 μs.…”
Section: Methodsmentioning
confidence: 99%
“…Steered MD provides an atomistic view for experimental results obtained with single-molecule atomic force microscopy (AFM)-based force spectroscopy [87]. One well-studied model system is the immunoglobulin domain I27 of titin, a giant protein (about 30,000 amino acid residues) responsible for the contraction and extension of muscles [8890]. In particular, the height of the potential energy barrier [89] and the additional effect of temperature during pulling was determined [88].…”
Section: Simulation Of Folding/unfolding Under More Complex Conditmentioning
confidence: 99%
“…One well-studied model system is the immunoglobulin domain I27 of titin, a giant protein (about 30,000 amino acid residues) responsible for the contraction and extension of muscles [8890]. In particular, the height of the potential energy barrier [89] and the additional effect of temperature during pulling was determined [88]. Steered MD and force spectroscopy have also recently cooperated to reveal multiple pathways in the unfolding of a slipknotted protein [91].…”
Section: Simulation Of Folding/unfolding Under More Complex Conditmentioning
confidence: 99%